2015
DOI: 10.1016/j.ijimpeng.2015.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of penetration in polyethylene reinforced cross-ply laminates

Abstract: A B S T R A C TThe mechanisms of progressive penetration for two ultrahigh molecular weight polyethylene (UHMWPE) reinforced laminates have been investigated. One used an UHMWPE fiber reinforcement while the other utilized molecularly aligned tape. Both materials had similar out of plane compressive strengths, but the fiber system had a 40% higher in plane tensile strength than the tape. Laminated, 6 mm thick plates with a [0°/90°] ply architecture were impacted by a 12.7 mm diameter sphere under conditions th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 30 publications
5
42
0
Order By: Relevance
“…Despite the challenges associated with the accurate characterization of these materials, a good number of investigators have made advances in testing these unique materials. Simple uniaxial tensile tests of [0/90] and [+45/-45] UHMWPE laminates have been successfully performed, but difficulties associated with gripping the material have led to the development of specialized fixtures and specimen configurations to apply the axial loading [1][2][3][4][5][6]. Success has also been reported on the characterization of UHMWPE composite compression behavior [6][7][8] as well as Mode I and II fracture toughness [4,9].…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…Despite the challenges associated with the accurate characterization of these materials, a good number of investigators have made advances in testing these unique materials. Simple uniaxial tensile tests of [0/90] and [+45/-45] UHMWPE laminates have been successfully performed, but difficulties associated with gripping the material have led to the development of specialized fixtures and specimen configurations to apply the axial loading [1][2][3][4][5][6]. Success has also been reported on the characterization of UHMWPE composite compression behavior [6][7][8] as well as Mode I and II fracture toughness [4,9].…”
Section: Motivation and Backgroundmentioning
confidence: 99%
“…The progressive penetration mechanism of ultra-high molecular weight polyethylene reinforced cross-ply composite laminates was investigated by O'Masta et al [17]. They observed that sample penetration occurred by tensile ply rupture under the projectile, and higher penetration resistance and onset velocity occurred as the consequence of the sample being end-supported rather than back-supported.…”
Section: Introductionmentioning
confidence: 99%
“…Different failure mechanisms under bullet penetration occurring in high-modulus high-strength polymeric materials have been revealed in the literature. These mechanisms have been phenomenologically described in several papers such as [1] and [2], and have been highlighted in photographs by various authors, including [3,4]. These mechanisms include cutting of the material fibres or filaments (also known as 'punching' [1]), stretching accompanied by deflection of the panel, friction between the bullet and its surrounding, energy transfer by the waves away from the impact, etc.…”
Section: Introductionmentioning
confidence: 99%